Sosialisasi Belajar Berorganisasi yang Bermakna dengan Memahami Peran Lembaga Sosial pada Siswa SMK Muhammadiyah 04 Boyolali - Arneta Wahyu Prabawati; Laudya Saraswati; Rizka Khoirunnisa Susanto; Siti Afifah Romadhoni; Zulaika Ratih Widhianti; Unna Ria Safitri (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Student organizations in schools play an important role as social institutions that support character building and the development of students’ social and leadership skills. However, in practice, many students still perceive school organizations merely as formal or administrative activities, resulting in low participation and limited understanding of their educational value. This condition highlights the need for socialization activities that emphasize meaningful organizational learning. This community service activity aims to strengthen students’ understanding of the role of school organizations as social learning spaces. A descriptive qualitative approach was employed involving 30 eleventh-grade students at SMK Muhammadiyah 04 Boyolali. Data were collected through observation, discussion notes, and students’ responses during interactive sessions.The activity was conducted through teacher coordination, material preparation, material presentation, and discussion and question-and-answer sessions. The results indicate an improvement in students’ understanding of the functions and benefits of student organizations as social institutions. Students showed increased awareness of the importance of cooperation, discipline, responsibility, and communication, as well as greater motivation to actively participate in school organizations. These findings suggest that participatory and dialogical socialization is effective in promoting meaningful organizational learning and supporting students’ character development.